STRATEGI KEBIJAKAN PERTUMBUHAN HIJAU (GREEN GROWTH) INDONESIA: DALAM ADAPTASI PERUBAHAN IKLIM - Dewi Ayu Marchela Putri; Langgeng Rachmatullah Putra (Journal Publicuho, 2024)
The purpose of this research is to understand and discuss Indonesia's green growth strategies in facing global challenges related to climate change The main focus of this study lies in policy adaptation and practices that support climate change mitigation and adaptation, taking into account both local and global contexts. Through secondary data analysis, this article identifies the main challenges faced by Indonesia, such as increasing greenhouse gas emissions and deforestation Additionally, the article evaluates government and private sector initiatives in promoting renewable energy, natural resource conservation, and enhancing community adaptation capacity. Research findings indicate that the success of Indonesia's green growth strategy heavily relies on multisectoral collaboration, increased public awareness, and strong political commitment The conclusion of this article emphasizes the need for a holistic and inclusive approach in designing policies and implementing them to achieve sustainable economic growth and climate resilience.